Extracellular Vesicles From Sporothrix brasiliensis Are an Important Virulence Factor That Induce an Increase in Fungal Burden in Experimental Sporotrichosis - Ikeda, Marcelo Augusto Kazuo; de Almeida, José Roberto Fogaça; Jannuzzi, Grasielle Pereira; Cronemberger-Andrade, André; Torrecilhas, Ana Cláudia Trocoli; Moretti, Nilmar Silvio; da Cunha, Julia Pinheiro Chagas; de Almeida, Sandro Rogério; Ferreira, Karen Spadari (Frontiers in Microbiology, 2018)
Sporotrichosis is a mycosis that affects the skin, lymphatic system and other organs in humans and animals. The disease has a worldwide distribution, with endemic areas in Brazil, and is caused by a complex of species, including Sporothrix brasiliensis. Some fungi release extracellular vesicles (EVs) that can interact with the host cell and modulate the host immune response. The aim of this study was to analyze the participation of S. brasiliensis EVs in the modulation of dendritic cells (DCs) and in the control of infection in vivo. Our results showed that in vitro, the EVs isolated from S. brasiliensis induced an increase in the phagocytic index and fungal burden in DCs. In addition, we observed a significant increase in IL-12p40 and TNF-α cytokine production. Then, the EVs were inoculated into BALB/c mice before subcutaneous infection with yeast, and the lesion was analyzed after 21, 35 and 42 days. An increase in fungal burden and lesion diameter were observed after 21 days in mice inoculated with a high concentration of EVs. However, after 35 days, we observed a regression of the lesion, which persisted until 42 days after infection. Interestingly, we observed an increase in fungal burden in these mice. In addition, we observed the presence of immunogenic components and proteins that could be related with virulence in EVs. These results suggest that EVs can play an important role in virulence and modulation of the host immune system during experimental S. brasiliensis infection.